Left. No. 76, What they say about the Beveridge Report ([London : Controversy Pub. Co.])
1943-01 1943 1940s 8 pages Sir William Beveridge told the Fabian Society that he is against any form of Soviet Communism. But surely the only real solution to our problems is going to be planned production for commodity consumption, which is what the Russians have. The Beveridge Plan will fall between two stools. On the one hand, the vested interests will fight it. On the other, people will come more and more to see that planned production is the only way out. After this war you will see that in this country planned reconstruction will have powerful enemies. On the other hand, in Soviet Russia, reconstruction has no enemies. They will simply get on with the job. And that will make more and more converts. Without planning, Capitalist countries after this war are going to suffer from unemployment, underemployment and — in Britain particularly — a falling birthrate. I do not know what is going to happen here after the war, but I fear it is going to be rather tragic. I can see the world faced with many questions which the war has aggravated. Decline of birthrate, unemployment, the racial question. And I come back to this — you cannot run away from it — that apart from being good fighters the Russians have found solutions for these problems. Harry Pollitt, in the Daily Worker (4.12.42). — The Beveridge proposals attack very important vested interests against which the most strenuous fight will have to be conducted and we shall support that fight to the utmost limit. They also depend for their successful application on the fact that capitalism after the war will be able to solve the problem, which so far it has never been able to solve, viz., economic crisis, and we shall also point out this fact so that there can be no illusion spread amongst the working-class. They do, however, represent a social advance which in their entirety can only be successful in the degree to which they are made the unified aim of progressive people and this we will support with all our strength. We shall campaign for reducing the obligations imposed upon the workers under the Beveridge scheme and increase those of the State as the monopolist. Campbell Stephen, in the New Leader (19.12.42). — Some have hailed the Plan as a great instalment of Socialism. It is no such thing. At its best it is an attempt to mitigate some of the evils resulting from the capitalist economic system. But it leaves that economic system in full being, and grave doubts may be entertained as to how far it can work in the present economic structure. Sir William Beveridge declares that he assumes as his third assumption for the success of his scheme that there will be no mass unemployment. The plain fact of the matter is that unless we change the basis of our economic system we shall have to face the possibility, nay, probability, of mass unemployment in the post-war years as formerly. Then the finances of the scheme will break down. Benefits will have to be reduced and contributions increased, and the promised economic security on a subsistence basis will vanish. 11 172/BE/7